Busan Biennale 2006 : Busan Sculpture Project- Homage to the Earth - Busan Biennale (Gyeonggi-do, Korea; Artbooks Publishing, 2006)
Exhibition Catalog. Texts: Tae-ho Lee, Tae-man Choi.
English; Korean
Keywords: N4390-5098 Visual Arts- Exhibitions